Investigating the Performance of Resistance Economy Policy in Iran: A Study of the Coordination Failure - Seyed Ehsan Khandoozi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Part of the goals of a resistance economy is interdisciplinary, that is, it requires the cooperation of various actors in the field of policy and bureaucracy. The evidence presented in this paper shows that one of the obstacles to realize a resistance economy in Iran is the coordination failure which follows the issue of government failure in the public sector economics. This paper, while reviewing the theoretical framework of this phenomenon in the conventional literature, points to two categories of coordination failure in Iran and its effects on long-term performance indicators. Failure to implement industrial development policy, failure to improve productivity, failure to combat economic corruption, failure to manage foreign trade and imports, weakness in solving the problem of unauthorized credit institutions and lack of water governance are examples mentioned in this article. At the end, policy suggestions have been introduced to reduce the degree of coordination failures.